Age-faking and match-fixing: how table tennis trainers and players face gold-medal pressure in China - Boucher, A. (Deviant Behavior, 2023)
The present research discusses the falsification of athletes` birthdates in Chinese table tennis and a specific case of match fixing. It investigates why athletes and trainers who faced pressure on performance gave-up match-fixing opportunities, while they have adopted age faking. Based on interviews with the trainers and athletes who considered those alternatives, we show that match fixing did not develop because trainers were worried about a potential moral entrepreneur who had both the interest and power to complain publicly. On the contrary, age faking developed because it aligned the interests of the trainers and athletes belonging to a given institution and conformed to the groups` ethic. In these circumstances, trainers and athletes have transformed "age faking" into a "collective hypocrisy," that is a collectively acknowledged and covered practice providing a competitive advantage and presented as a way to maintain virtue.